Deciphering the Glycosylation Steps in the Biosynthesis of P-1894B and Grincamycin Isolated from Marine-Derived IStreptomyces lusitanus/I SCSIO LR32 - Huang, Hongbo; Zhang, Yun; Song, Yongxiang; Ling, Chunyao; Peng, Siyan; Ding, Bo; Tao, Yiwen; Ju, Jianhua (Marine drugs, 2024)
Recently, we re-isolated the glycosylated angucycline antibiotics P-1894B (1) and grincamycin (1′) from the marine-derived Streptomyces lusitanus SCSIO LR32 as potent antitumor agents and identified their biosynthesis gene cluster gcn. Both P-1894B (1) and grincamycin (1′) possess a trisaccharide and a disaccharide moiety comprised of five deoxysugars. In this work, three genes encoding glycosyltransferases (GcnG1, GcnG2, and GcnG3) responsible for the assembly of deoxysugars into angucycline aglycone were identified from the biosynthesis gene cluster gcn. Gene inactivations of gcnG1, gcnG2, gcnG3, and gcnG1G2 by lambda-RED-mediated gene replacements led to the construction of four mutants, in which the glycosyltransferase genes were disrupted, respectively. The metabolites from the mutants were purified and identified, including two new analogues designated as grincamycin U (3a) and V (3′). The sequential glycosylation steps in the biosynthesis of P-1894B (1) and grincamycin (1′) catalyzed by GcnG3, GcnG1, and GcnG2 were elucidated.